(untitled) (Bangladesh Journal of Agricultural Research, 2019)
The field experiment was conducted at Regional Agricultural Research Station (RARS), Hathazari, Chattagram to find out the efficacy of integration of poultry refuse (PR) with stable bleaching powder (SBP) or CaNO3 and Furadan 5G for the management of bacterial wilt (Ralstoniasolanacearum) and root-knot nematode disease (Meloidogyne incognita) of brinjal. Soil was treated with PR @ 3 t/ha 3 weeks before transplanting, stable bleaching powder @ 20 kg/ha during final land preparation and Furadan 5G @ 20 kg/ha on the day of seedlings transplanting while CaNO3 was used as soil drenching 10 days after seedling transplanting. Results showed that integration of poultry refuse with Furadan 5G and stable bleaching powder or CaNO3 reduced root-knot and bacterial wilt diseases and increased plant growth as well as yield of brinjal. The most effective treatment combination was PR + stable bleaching powder + Furadan 5G with early sowing, followed by PR + CaNO3 + Furadan 5G with early sowing for the management of bacterial wilt and root knot nematode diseases and increasing plant growth and yield of brinjal. The technology, poultry refuse+ stable bleaching powder + Furadan 5G was validated at Bangladesh Agricultural Research Institute (BARI), Gazipur, Regional Agricultural Research Station of Jessore, Hathazari and Jamalpur and also at Agricultural Research Station and farmers field at Burirhat, Rangpur and OFRD farm at Alamnagar, Rangpur. The validation trials showed that integration of poultry refuse + stable bleaching powder+ Furadan 5G in early sowing was an effective management package of bacterial wilt and root knot nematode diseases of brinjal which also offered 21.81 to 25.98% higher yield over the conventional practices. Bangladesh J. Agril. Res. 44(3): 427-437, September 2019